Polarization behavior of bone marrow-derived macrophages on charged P(VDF-TrFE) coatings. (25th November 2020) - Wang, Zhiying; He, Xuzhao; Tang, Bolin; Chen, Xiaoyi; Dong, Lingqing; Cheng, Kui; Weng, Wenjian
Abstract : The immune response of bone implants is closely related to the interaction between macrophages and biomaterial surfaces. Abstract : The immune response of bone implants is closely related to the interaction between macrophages and biomaterial surfaces. In this work, the polarization behavior of mouse bone marrow-derived macrophages (BMDMs), including their morphology and expression of phenotypic markers, genes and cytokines, on charged surfaces with different potential intensities was systematically explored. We found that the charged surface could effectively promote BMDM polarization, and a higher potential intensity was conducive to the upregulation of the polarization of BMDMs into the M2 phenotype. Based on the analysis of the signaling pathways involved in integrins (αMβ2 and α5β1) and the potassium ion channel (Kv1.3), a possible underlying mechanism revealed that the integrin originated signaling pathways could more dominantly regulate macrophage polarization to the M2 phenotype. The present work therefore demonstrates that the surface charge, as a physicochemical property of material surfaces, could effectively regulate macrophage polarizations, which may provide an immunoregulation view for the surface design of biomaterials.